Eksistensi Komisi Yudisial dalam Pengawasan Hakim (Tinjauan Yuridis dan Hukum Islam terhadap Undang-Undang No. 18 tahun 2011) - Indra Utama Tanjung (Al-Fikru: Jurnal Ilmiah, 2021)
This study aims to analyze the existence of the judicial commission on the supervision of judges in Law no. 18 of 2011 concerning the Judicial Commission. The research method used in this study is a qualitative method using a literature study approach. The main data source used is Law no. 18 of 2011 concerning the Judicial Commission and the Law on Amendments to Law Number 22 of 2004 concerning the Judicial Commission. Data analysis is carried out by comparing the existence of the judicial commission from the two legal sources, and then drawing conclusions about the existence of the judicial commission, and its function of supervising judges. The results of the study indicate that the change to Law No. 22 of 2004 is the answer to the ambiguity of the duties, authorities and functions of the Judicial Commission, because it is not clear enough what is meant by "other powers in order to maintain and uphold honor, dignity, and behavior". judge." The problem becomes clearer, if the other authority is interpreted as supervision, because in the laws and regulations there are other institutions (besides the Judicial Commission) which are given the authority to carry out supervision. It is also in the context of maintaining and upholding the honor, nobility of dignity, and the behavior of judges is supervision.